EFFECT OF SURFACTANT ON FABRICATION OF CORE-SHELL STRUCTURED MESOPOROUS SILICA NANOPARTICLES - relv; Ngoc Huyen Nguyen Thi; Xuan Thi Diem Trinh Nguyen; Nguyen Minh Thao (HUIT Journal of Science, 2025)
Hollow mesoporous silica nanoparticles (HMSN) were synthesized by the hard-template method, consisting of three stages: forming a solid silica nano core (SSN), developing a coreshell structure (SSN@CTAB-SSN), and etching the core to form hollow silica nanoparticles. This study evaluated the effect of surfactant (Cetyltrimethylammonium Bromide – CTAB) in the second stage on forming core-shell structured silica nanoparticles. Transmission electron microscopy (TEM) characterization showed that no core-shell structure formed when no surfactant was used, and the coating mechanism was clearly explained. SSN@CTAB-SSN particles were about 160.6 ± 0.8 nm, with the shell having a size of about 60 nm. The zeta potential and stability were measured by dynamic light scattering (DLS), which was +31.5 ± 0.7 mV.